Objects Over People - Salma Abumeeiz (Canadian Journal of Academic Librarianship)
There is a tradition and practice in libraries and other Western and information institutions of collecting, stewarding, and taking “cultural heritage” materials from non-Western communities or about non-Western subjects. Attention to the practice of collecting cultural heritage is heightened during times of perceived threat, vulnerability, or destruction of these materials, and the ways in which libraries and memory workers can intervene in their protection. Framed as removal and rescue, the practice and narrative around absorbing “at risk” heritage materials reveals a set of assumptions about how libraries and information institutions attempt to decontextualize themselves from the world; this essay will unpack this framing, its outcomes, whose interests it serves, and the kinds of politics it extends and legitimizes. Utilizing textual analysis of mainstream library guidelines and communications, and drawing on principles of critical librarianship, art criticism, and anti-colonial writing, which point to the embeddedness of library and information work within regimes of power, this chapter will problematize the tendency of our fields to deploy rhetorics of inclusion—and the politics that underpin that rhetoric—in its justification of heritage absorption and representation, namely, that it inherently contributes to a social justice project, is universally desired, and serves an imagined “public good.”